Pengabaian Orang Tua Terhadap Anak Usia Dini Dalam Aktivitas Menjelang Tidur di Kota Serang - Dian Surya Aprilyanti (Journal on Education, 2023)
Bedtime is the time awaited not only by children but also by adults. However, in some conditions, children need time and often when children have trouble sleeping, adults are tired and prone to neglecting children before going to bed. Neglect is a situation or condition in which a child's needs are not met either physically or spiritually. There are 3 goals for children to avoid neglect by adults, first to keep children away from stress in life, second to provide children with protection, stimulation and positive parenting, third to guide children to be independent (Wade. M, et al 2019). Mistakes in bedtime routines such as the absence of routines in maintaining cleanliness before going to bed, communicating and telling stories before going to bed so that children play gadgets or use information communication media until bedtime can cause health problems both physically and psychologically. So in this study discussed how should the routine of children before going to sleep in order to get good quality sleep that supports the growth and development of children.